2014
DOI: 10.1007/s11605-014-2560-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Intraoperative Cholangiography Using Indocyanine Green (Versus Contrast Fluid) for the Correct Assessment of Extrahepatic Bile Ducts During Day-Case Laparoscopic Cholecystectomy

Abstract: IOC-IG was feasible and safe. Our results suggest that this technique is more effective than IOC-CF for biliary tract identification after dissection and may constitute a powerful diagnostic test for the detection of extrahepatic ducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
0
20
0
4
Order By: Relevance
“…Second, overall visualization rates of the CD and CBD with NIR fluorescence were much lower than the visualization rates described for uncomplicated cases of cholecystolithiasis. 24-38 …”
Section: Discussionmentioning
confidence: 99%
“…Second, overall visualization rates of the CD and CBD with NIR fluorescence were much lower than the visualization rates described for uncomplicated cases of cholecystolithiasis. 24-38 …”
Section: Discussionmentioning
confidence: 99%
“…Ishizawa and colleagues first described intraoperative fluorescence cholangiography. Several groups have found fluorescence cholangiography to be feasible, but it has not been validated against X‐ray cholangiography.…”
Section: Introductionmentioning
confidence: 99%
“…Several dosage schemes were used: a fixed dosage of 2.5 mg ICG was used in nine studies [16, 26, 27, 31, 33, 35, 3739], a dosage of 0.05 mg/kg bodyweight was used in six studies [2830, 32, 34, 40], a dosage of 0.5 mg/kg bodyweight was used in two studies [25, 36] and two studies reported other dosage schemes [15, 41]. For analysis of biliary tract identification, the studies providing information on dosage scheme were stratified by fixed dosage (2.5 mg) and dosage per kilogram bodyweight (0.05 mg/kg) as given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…No studies reported on the CHD and CD-j visualization after dissection. Two studies have used a dosage scheme of 0.5 mg/kg bodyweight, of which one has evaluated visualization of the biliary structures before and after dissection in 23 patients [36]. Two included studies with different dosage schemes [15, 41] did not report on biliary tract visualization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation